Varieties of economic constitutionalism and the alternative of conflicts-law constitutionalism: observations on the conceptual history of the law of the integration project - Christian Joerges (European Law Open)
This article pursues re-constructive and explanatory objectives which are embedded in a theoretical and normative agenda. The introduction specifies its beginnings including biographical notes. The following conceptual history of the law of the integration project distinguishes three stages in which three distinct varieties of economic constitutionalism have been pursued, which all remained defective when measured against the commitments to democracy, social justice, and the rule of law. These defects deepened in the managerial responses to the financial crisis of 2008. Throughout the article, a counter vision of conflicts-law constitutionalism is developed step by step. The final section of the article seeks a theoretical backing for this counter vision in Lisa Herzog’s theory of ‘democratic institutionalism’. The epilogue sketches out how the project will continue.